2015
DOI: 10.1002/anie.201506592
|View full text |Cite
|
Sign up to set email alerts
|

Copying of RNA Sequences without Pre‐Activation

Abstract: Template-directed incorporation of nucleotides at the terminus of a growing complementary strand is the basis of replication. For RNA, this process can occur in the absence of enzymes, if the ribonucleotides are first converted to an active species with a leaving group. Thus far, the activation required a separate chemical step, complicating prebiotically plausible scenarios. Here we show that a combination of a carbodiimide and an organocatalyst induces near-quantitative incorporation of any of the four ribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 47 publications
2
93
0
Order By: Relevance
“…As reported in Ref. 14, we have found that a combination of the water-soluble carbodiimide EDC and alkylated heterocycles, such as 1-ethylimidazole, induces copying processes in RNA via in situ activation of ribonucleotides, without the need for chemical pre-activation. Carbodiimide is a tautomer of cyanamide, a compound formed under presumed prebiotic conditions 15.…”
supporting
confidence: 60%
“…As reported in Ref. 14, we have found that a combination of the water-soluble carbodiimide EDC and alkylated heterocycles, such as 1-ethylimidazole, induces copying processes in RNA via in situ activation of ribonucleotides, without the need for chemical pre-activation. Carbodiimide is a tautomer of cyanamide, a compound formed under presumed prebiotic conditions 15.…”
supporting
confidence: 60%
“…On the other hand, Richert and coworkers reported the use of benzotriazole-activated monomers to improve the rate of primer extension (8). In an alternative approach, the in situ activation of monoribonucleotides, and subsequent template-guided polymerization, has been achieved by Richert and coworkers (9), using a carbodiimide reagent together with N-alkyl-imidazole catalysts.…”
mentioning
confidence: 99%
“…The drawback of this approach lies in the number of additional reaction components and the formation of side products that might interfere with the condensation reaction [23]. Water-soluble carbodiimides, like 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) [24] and hydroxy-7-azabenzotriazole (HOAt), have been used [25,26,27]. In the laboratory, 10 molar equivalents of EDC for guanine monomers and 50 molar equivalents for thymidine/uridine monomers are however required to yield an efficient coupling [23].…”
Section: Rna World Hypothesismentioning
confidence: 99%
“…The hybridization can force the template into an A-helix form for RNA that clearly enhances the rates [45], and the primer offers a base-stacking surface for the new approaching base, which will improve monomer association with the templating sequence. In a few studies [24,25,46], the interactions between the incoming monomer and template at the 3′ end of the primer were strengthened by the addition of short oligomers (4 to 6 nt) that hybridized downstream from the monomer insertion point (System (iii)): in such a system, the incoming monomer is associated more tightly with the template due to the increased stacking, hence increasing its probability to be linked to the primer. However, this last system should be viewed as a technological fix to improve sequence-specific monomer incorporation than a truly plausible prebiotic setup.…”
Section: Rna Polymerization In Bulk Aqueous Mediamentioning
confidence: 99%
See 1 more Smart Citation